Development of Tourism in Local Communities: A Systematic Review of Literature on Tourism Development with Collaborative Management in Rural Areas - Tjaša Glažar (Naše gospodarstvo/Our economy, 2026)
This integrative literature review explores the relationship between community-based tourism (CBT) development and local community involvement, focusing on collaborative management in rural areas. Following PRISMA 2020 guidelines, 27 peer-reviewed articles—24 empirical and 3 review papers—published in English between 2020 and 2024 were analysed using qualitative content analysis. Active engagement of local communities as co-creators enhances sustainability outcomes, fosters cultural preservation, and improves socio-economic well-being, while challenges include institutional weaknesses, demographic shifts, and limited financial resources. The review is restricted to recent English-language publications and secondary data, potentially omitting earlier or regional studies. Results offer actionable insights for policymakers, destination managers, and researchers to design inclusive governance models. By integrating empirical and review studies across diverse contexts, this review identifies governance gaps and proposes strategies, including comparative policy research, standardized evaluation frameworks, and digital engagement tools, to strengthen CBT in rural settings.